Screening, Competition, and Job Design - Björn Bartling; Ernst Fehr; Klaus M. Schmidt (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2010)
In recent decades, many firms offered more discretion to their employees, often increasing the productivity of effort but also leaving more opportunities for shirking. These “high-performance work systems” are difficult to understand in terms of standard moral hazard models. We show experimentally that complementarities between high effort discretion, rent-sharing, screening opportunities, and competition are important driving forces behind these new forms of work organization. We document in particular the endogenous emergence of two fundamentally distinct types of employment strategies. Employers either implement a control strategy, which consists of low effort discretion and little or no rent-sharing, or they implement a trust strategy, which stipulates high effort discretion and substantial rent-sharing. If employers cannot screen employees, the control strategy prevails, while the possibility of screening renders the trust strategy profitable. The introduction of competition substantially fosters the trust strategy, reduces market segmentation, and leads to large welfare gains for both employers and employees.
urn:nbn:de:bvb:19-epub-11312-2
Keywords: C91; D86; 330; job design; high-performance work systems; screening; reputation; competition; trust; control; social preferences; complementarities; Arbeitsgestaltung; Kooperative Führung; Leistungsbeurteilung; Vertrauen; Wettbewerb; Reputation; Prinzipal-Agent-Theorie; Soziale Wohlfahrtsfunktion; Test